Brachial artery Doppler flux parameters before and after hot flush in Mexican postmenopausal women: preliminary report - Carranza-Lira, Sebastián; Rodríguez, Karina Vázquez; Rosales Ortiz, Sergio (Menopause Review/Przegląd Menopauzalny, 2016)
Objective : To analyse brachial artery flux parameters in postmenopausal women before and after hot flush. Material and methods : Two groups of postmenopausal women were studied: Group I, without vasomotor symptoms (n = 10) and Group II, with vasomotor symptoms (n = 10). In all them a brachial artery Doppler ultrasound was done, measuring before and after hyperaemic stimulus of the arterial diameter (AD), the pulsatility index (PI), and the resistive index (RI). In Group I, measurements were done at baseline and five minutes after. In Group II, measurements were at baseline, and one and five minutes after the hot-flush. Comparison between the groups was done with Mann-Whitney U test, and within the groups with Wilcoxon test. Results : No differences were found among the groups in Doppler parameters. When comparing each group separately, in Group I, at baseline and at five minutes measurements, the AD was greater after the hyperaemic stimulus than before it. In group II at baseline, the PI was significantly greater after the hyperaemic stimulus than before to it. At the first and fifth minute, the AD was significantly greater after the hyperaemic stimulus than before to it. Conclusions : No differences were found between those who did not have and those who had hot flushes.